1997
DOI: 10.1029/96jb02856
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkle‐like slip pulse on a fault between different materials

Abstract: can be generated as a secondary effect of a droi• of shear stress in an asperity. The pulse shape is unstable, and the initial slip pulse can change during propagation into a collection of sharper pulses. Such a pulse enables slip to occur with little loss of energy to friction, while at the same time increasing irregularity of stress and slip at the source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
328
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(354 citation statements)
references
References 31 publications
24
328
1
1
Order By: Relevance
“…Cochard and Rice (2000) showed that the model which Andrews and Ben-Zion used, with constant friction coe cient, would not give numerical convergence with grid reÿnement, due to the ill-posedness discussed. Cochard and Rice (2000) also showed that a reformulation of the problem using the regularized friction law of Ranjith and Rice (2001) did lead to convergent solutions with properties somewhat like those suggested by Andrews and Ben-Zion (1997). Extensive further studies along those lines, using the same regularized friction law, are reported by Ben-Zion (2001).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Cochard and Rice (2000) showed that the model which Andrews and Ben-Zion used, with constant friction coe cient, would not give numerical convergence with grid reÿnement, due to the ill-posedness discussed. Cochard and Rice (2000) also showed that a reformulation of the problem using the regularized friction law of Ranjith and Rice (2001) did lead to convergent solutions with properties somewhat like those suggested by Andrews and Ben-Zion (1997). Extensive further studies along those lines, using the same regularized friction law, are reported by Ben-Zion (2001).…”
Section: Introductionmentioning
confidence: 74%
“…Andrews and Ben-Zion (1997) reported numerical simulations of highly unstable slip pulses along interfaces between dissimilar materials that were shear-loaded below the friction threshold. Cochard and Rice (2000) showed that the model which Andrews and Ben-Zion used, with constant friction coe cient, would not give numerical convergence with grid reÿnement, due to the ill-posedness discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Andrews and Ben-Zion [1997] demonstrated through numerical simulations that these asymmetries can lead to emergence of a self-sustaining slip pulse (the ''wrinkle pulse'') propagating unilaterally in the positive direction, as proposed by Weertman [1980]. Those simulations were for a simplified model in which the friction coefficient never weakens at or following the onset of sliding, so the asymmetrical wrinkle pulse dominates the dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Rupture at the interface between solids of contrasting elastic compliance has been the subject of extensive theoretical and numerical studies [e.g., Weertman, 1980;Adams, 1995;Andrews and Ben-Zion, 1997;Harris and Day, 1997;Cochard and Rice, 2000;Ranjith and Rice, 2001;Ma and Beroza, 2008;Ampuero and Ben-Zion, 2008], as well as scale-model experiments [Xia et al, 2005]. In a propagating mode II rupture, the compliance contrast induces a normal stress perturbation proportional to the slip gradient [Weertman, 1980], which can be large near the rupture front.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on these structural components because they contain information on likely properties of past and future earthquake ruptures and associated ground motion (e.g. Andrews & Ben-Zion 1997;Dor et al 2006Dor et al , 2008Brietzke et al 2009;Shlomai & Fineberg 2016).…”
Section: Introductionmentioning
confidence: 99%